Сезонная динамика морфо-физиологических показателей сусликов трех южноукраинских популяций - Филипчук, Н.С. (Вестник зоологии, 1973)
The age, sexual and seasonal variability of interior and exterior characters was studied in Citellus pygmaeus P a l l. and C. suslicus G u l d. from the agrobiocenoses populations in the Crimean, Kherson and Nikolaev regions. Investigations performed on 382 animals resulted in establishing species specificity of morpho-prysiologcal characters. Sexual dimorphism was marked for the species by a number of characters. A regular decrease in the relative weight of viscera with age was observed in both species. The characters under investigation are subjected to seasonal variability.